Analyzing the 3D chromatin organization coordinating with gene expression regulation in B-cell lymphoma - Luis Augusto Eijy Nagai; Sung-Joon Park; Kenta Nakai (BMC, 2019)
Abstract Background Eukaryotes compact chromosomes densely and non-randomly, forming three-dimensional structures. Alterations of the chromatin structures are often associated with diseases. In particular, aggressive cancer development from the disruption of the humoral immune system presents abnormal gene regulation which is accompanied by chromatin reorganizations. How the chromatin structures orchestrate the gene expression regulation is still poorly understood. Herein, we focus on chromatin dynamics in normal and abnormal B cell lymphocytes, and investigate its functional impact on the regulation of gene expression. Methods We conducted an integrative analysis using publicly available multi-omics data that include Hi-C, RNA-seq and ChIP-seq experiments with normal B cells, lymphoma and ES cells. We processed and re-analyzed the data exhaustively and combined different scales of genome structures with transcriptomic and epigenetic features. Results We found that the chromatin organizations are highly preserved among the cells. 5.2% of genes at the specific repressive compartment in normal pro-B cells were switched to the permissive compartment in lymphoma along with increased gene expression. The genes are involved in B-cell related biological processes. Remarkably, the boundaries of topologically associating domains were not enriched by CTCF motif, but significantly enriched with Prdm1 motif that is known to be the key factor of B-cell dysfunction in aggressive lymphoma. Conclusions This study shows evidence of a complex relationship between chromatin reorganization and gene regulation. However, an unknown mechanism may exist to restrict the structural and functional changes of genomic regions and cognate genes in a specific manner. Our findings suggest the presence of an intricate crosstalk between the higher-order chromatin structure and cancer development.